The effects of amlodipine on exercise performance in mild to moderate essential hypertensives - Gillies, Hunter Campbell (MRC/UCT RU for Exercise and Sport Medicine, 2018)
The effect of the long acting dihydropyridine calcium channel antagonist, amlodipine, on the exercise performance of hypertensive patients is not known. The aim of this study was to determine the effects of amlodipine on maximal (MAX), prolonged submaximal (PSX) and on skeletal muscle function (SMF) in patients with mild hypertension. In a double-blind randomised crossover trial, ten physically active hypertensive patients performed i) graded exercise to exhaustion for determination of maximal oxygen consumption (VO₂ₘₐₓ), peak heart rate (HR) and systolic blood pressure (SBP); ii) PSX at 75% VO₂ₘₐₓ to determine, cardiorespiratory responses, cardiac output (Q), blood lactate [La], free fatty acid [FFA], glucose [G] concentrations and ratings of perceived exertion (RPE), and iii) tests of isometric SMF including maximal voluntary contraction (MVC) and time to fatigue (TTF) during repetitve isometric MVC's. Tests were performed following two week ingestion of amlodipine (5 mg daily) or placebo seperated by a two week washout period. Resting SBP was decreased following ingestion of amlodipine (142 ± 13 vs l33 ± 12 mmHg; vs placebo: [mean± SD]; P<0.05). However, VO₂ₘₐₓ ( 31 ± 5 vs 33 ± 5 mlO₂.kg.min⁻¹ ; amlodipine vs placebo), peak heart rate ( 167 ± 12 vs 165 ± l6b.min⁻¹;amlodipine vs placebo)and peak SBP(l8l ±21 vs 170± 16mmHg; amlodipine vs placebo) were not reduced following ingestion of amlodipine. Submaximal cycling time. VO₂, Q, BP, HR, ventilation, RPE, [FFA], [La] and [G] during PSX were unaltered following ingestion of amlodipine. Similarly ingestion of amlodipine did not alter tests of isometric SMF. These data suggest that: i) ingestion of amlodipine lowers resting SBP but does not alter the normal haemodynamic response during exercise; ii) MAX, PSX exercise performance and SMF are unaltered following ingestion of amlodipine in athletic hypertensive patients. These findings suggest that the regulatory mechanisms which maintain haemodynamic homeostasis during maximal and submaximal exercise are not influenced by ingestion of amlodipine in athletic hypertensive patients.